EXPRESS: A Case of Portal Vein Thrombosis in a Cat with Partial Splenic Rotation and Intermittent Colonic Displacement - Hyuna Kim; YONGSUK JO; Joonghyun Song (Journal of Feline Medicine and Surgery Open Reports, 2026)
Case Summary: A 4-year-old neutered male Turkish Angora cat presented with lethargy, mental dullness and lower urinary tract signs. Hematological and biochemical analyses confirmed hepatic dysfunction. Diagnostic imaging identified portal vein thrombosis (PVT), an extrahepatic portosystemic shunt and collateral vessels surrounding the PVT. Additionally, partial splenic rotation and intermittent colonic displacement were identified. Primary hepatic disease, a common cause of PVT, could not be excluded in this patient, and visceral positional abnormalities were considered to have played a significant role in the development of PVT. Initial treatment consisted of anticoagulant therapy with rivaroxaban and symptomatic management of hepatic dysfunction and secondary complications. Following initiation of therapy, the patient maintained clinically stable with resolution of clinical signs despite persistent imaging evidence of PVT. Relevance and Novel Information: This is the first report in veterinary medicine to identify partial splenic rotation and intermittent colonic displacement as possible causes of PVT. Furthermore, this case demonstrates that a favorable clinical outcome may be achieved through conservative medical management of PVT secondary to abdominal visceral positional abnormalities.